HUBUNGAN KAPASITAS PETANI DENGAN KEBERHASILAN USAHATANI PADI SAWAH DI DESA LABULU-BULU KECAMATAN PARIGI KABUPATEN MUNA - Nurfian Nurfian; Awaluddin Hamzah; La Ode Kasno Arif (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to ascertain the correlation between farmer capacity and the efficacy of rice farming in Labulu-Bulu Village, Parigi District, Muna Regency. The population under study consists of 324 rice farmers residing in Labulu-Bulu Village. The sample size was determined using the Slovin formula with a margin of error of 15%, resulting in a sample of 39 respondents. The present study employs a quantitative research method. The data collection techniques employed in this study encompassed a range of methods, including in-depth interviews, documentation analysis, systematic literature reviews, and the administration of surveys. The research variables of interest were farmer capacity and the success of rice farming. The analysis was executed through the implementation of quantitative inferential analysis, specifically non-parametric statistics. The results of the study show that the capacity of rice farmers is proven to be in the high category, both in terms of knowledge, attitude, and skills, thereby supporting the success of rice farming, which is also in the high category in terms of social, economic, and environmental dimensions. The relationship between farmer capacity and farming success shows a moderate correlation, which means that the higher the capacity of farmers in managing their farms, the greater the success achieved. The success of farming is not only determined by production factors, but also by the capacity of individual farmers, which includes the ability to adapt to technological changes, sustainable resource management, and the application of environmentally friendly agricultural practices. Improving farmer capacity is key to promoting the success of rice farming, which is not only oriented towards production but also towards socio-economic sustainability and environmental preservation.